Making a living between crises and ceremonies in Tana Toraja : the practice of everyday life of a South Sulawesi highland community in Indonesia - Jong, Edwin Bernardus Paulus de, 1970- (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2013)
"The practice of everyday life in Tana Toraja (South Sulawesi, Indonesia) is structured by a series of public events, of which funerals are the most important. Even after Indonesia was hit by an economic crisis in the late 1990s, thousands of extravagant funeral ceremonies, requiring huge expenditures, were still organized each year. To understand the paradoxes and complexities of Torajan livelihoods, Edwin de Jong develops an approach that goes beyond existing economically biased perspectives on livelihoods by including both the cultural and the economic realm, positioned in the socio-political world with a transnational perspective, placed against a historical background, while not losing sight of diversity and individual creativity. It also advances the ethnography of Tana Toraja and the comparative study between numerous similar societies"--